HER2 testing in gastric cancer diagnosis: insights on variables influencing HER2-positivity from a large, multicenter, observational study in Germany - Baretton, Gustavo Bruno; Schirmacher, Peter; Gaiser, Timo; Hofheinz, Ralf-Dieter (Virchows Archiv, 2019)
HER2 testing in metastatic gastric or gastroesophageal junction cancer (mGC/mGEJC) is standard practice. Variations in HER2-positivity rates suggest factors affecting test quality; however, the influence of patient-, tumor-, and laboratory-related factors on HER2-positivity rates remains unknown. This observational, prospective study collected routine HER2 testing data from 50 pathology centers in Germany (January 2013-December 2015). For each sample, HER2 status, primary tumor location, method of sample retrieval, and other patient- and tumor-related parameters were recorded. A model for predicting the probability of HER2-positivity was developed using stepwise multiple logistic regression to identify influencing factors. Documented positivity rates and corresponding predicted HER2-positivity probabilities were compared to identify institutes with deviations in HER2-positivity. Data from 2761 mGC/mGEJC routine diagnostic specimens included 2033 with HER2 test results (1554 mGC, 479 mGEJC); overall HER2-positivity rates across centers were 19.8% and 30.5%, respectively. HER2-positivity correlated most with Lauren classification, then HER2 testing rate, primary tumor location, sample type, and testing method (all p < 0.05). Three institutes had model-predicted HER2-positivity rates outside the 95% confidence interval of their documented rate, which could not be explained by sample and center characteristics. Results demonstrated the high quality of routine HER2 testing in the mGC/mGEJC cohort analyzed. This is the first study investigating parameters impacting on HER2-positivity rates in mGC/mGEJC in routine practice and suggests that assessment of HER2 testing quality should consider primary tumor location, testing method and rate, and tumor characteristics. Accurate identification of patients with HER2-positive mGC/mGEJC is essential for appropriate use of HER2-targeted therapies.
Gesehen am 30.09.2019